Increase of upper troposphere/lower stratosphere wave baroclinicity during the second half of the 20th century - Castanheira, J; Añel, J; F Marques, C; Antũna, J; R Liberato, M; De La Torre, L; Gimeno, L (2009)
A strengthening of the equatorward temperature gradient in the upper troposphere/lower stratosphere (UTLS), at subtropics and midlatitudes, is consistently reproduced in several modelling studies of the atmospheric response to the increase of greenhouse gas radiative forcing. Some of those studies suggest an increase of the baroclinicity in the UTLS region because of the enhanced meridional temperature gradient. This study presents observational evidence of an increase of the baroclinic wave components of UTLS circulation (UTLS wave baroclinicity), during the second half of the 20th entury. The evidence is given by significant positive trends in the energy of baroclinic normal modes of the NCEP/NCAR reanalysis, and significant positive trends in the UTLS eddy available potential energy of the NCEP/NCAR, ERA-40, NCEP-2 and JRA-25 reanalyses. Significant positive trends in the frequency of double tropopause events in radiosonde data are also interpreted as a manifestation of an increase of the UTLS wave baroclinicity.